Influence of Photoperiod on the Behavior and Serum Proteins in Grey Quail (Coturnix Coturnix) - ESHITA PANDEY; V.L.SAXENA (International Journal of Pharma and Bio Sciences, 2010)
The present investigation focuses on the effects of photoperiod on general behavior and serum proteins in Quails taking them as a reference for other vertebrates. The present conditions of altered natural circadian rhythm and activity due to anthropogenic activities are creating a general condition of emphasized restlessness in organisms including the Aves. The behavioral changes observed due to induced conditions of acute photoperiod in Quails included refusal for food and water, vigorous activity and deliberate efforts to keep eyes closed. The banding pattern in the gel surfaces obtained after SDS-PAGE revealed significant changes showing definite presence of proteins being formed or inhibited due to stress conditions.